Analisis Pelaksanaan Program Kelompok Usaha Bersama (Kube) Di Kecamatan Katingan Hilir Kabupaten Katingan - Lies Fahimah; Nurul Hidayah (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2019)
This research aims to determine how to analyze the implementation of Joint Venture group Program in Katingan Hilir Sub-district of Katingan. The type of research used is a qualitative descriptive that is to explain a phenomenon that exists to solve a problem. In this research there are two data sources, namely primary data sources obtained from interviews with the head of the field of social empowerment and poor management of the social service of the regency of Katingan, the head of the section of stimulant aid assistance and Environmental arrangement of the social service of Katingan Regency, KUBE Companion of the lower Katingan subdistrict, and the community that received KUBE assistance in Katingan Sub-district. Based on the results of the study can be concluded that the implementation of the Joint Group program in Katingan Hilir Sub-district has not been maximized if the members of Kube that have not been properly targeted and implementation that have not fully participated Applicable. Advice (1) Integrated database (BDT) in order to renew each year so that KUBE assistance recipients are more precise (2) there is a regulation in the implementation of KUBE program (4) KUBE Companion in carrying out their duties to apply for the SOP that is in order to achieve Program objectives.